A Randomized Controlled Trial Comparing Different Sites of High-Velocity Low Amplitude Thrust on Sensorimotor Integration Parameters - Niazi, IK; Navid, MS; Merkle, C; Amjad, I; Kumari, N; Trager, RJ; Holt, K; Haavik, H (Springer Science and Business Media LLC, 2024)
Increasing evidence suggests that a high-velocity, low-amplitude (HVLA) thrust directed at a dysfunctional vertebral segment in people with subclinical spinal pain alters various neurophysiological measures, including somatosensory evoked potentials (SEPs). We hypothesized that an HVLA thrust applied to a clinician chosen vertebral segment based on clinical indicators of vertebral dysfunction, in short, segment considered as “relevant” would significantly reduce the N30 amplitude compared to an HVLA thrust applied to a predetermined vertebral segment not based on clinical indicators of vertebral dysfunction or segment considered as “non-relevant”. In this double-blinded, active-controlled, parallel-design study, 96 adults with recurrent mild neck pain, ache, or stiffness were randomly allocated to receiving a single thrust directed at either a segment considered as “relevant” or a segment considered as “non-relevant" in their upper cervical spine. SEPs of median nerve stimulation were recorded before and immediately after a single HVLA application delivered using an adjusting instrument (Activator). A linear mixed model was used to assess changes in the N30 amplitude. A significant interaction between the site of thrust delivery and session was found (F1,840 = 9.89, p < 0.002). Pairwise comparisons showed a significant immediate decrease in the N30 complex amplitude after the application of HVLA thrust to a segment considered “relevant” (− 16.76 ± 28.32%, p = 0.005). In contrast, no significant change was observed in the group that received HVLA thrust over a segment considered “non-relevant” (p = 0.757). Cervical HVLA thrust applied to the segment considered as “relevant” altered sensorimotor parameters, while cervical HVLA thrust over the segment considered as “non-relevant” did not. This finding supports the hypothesis that spinal site targeting of HVLA interventions is important when measuring neurophysiological responses. Further studies are needed to explore the potential clinical relevance of these findings.
Keywords: 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; 42 Health Sciences; 4208 Traditional, Complementary and Integrative Medicine; Chronic Pain; Neurosciences; Pain Research; Clinical Research; Neurodegenerative; Clinical Trials and Supportive Activities; Adult; Humans; Manipulation, Spinal; Cervical Vertebrae; Neck; Neck Pain; Nervous System Physiological Phenomena; Neck; Cervical Vertebrae; Humans; Neck Pain; Manipulation, Spinal; Adult; Nervous System Physiological Phenomena; Adult; Humans; Manipulation, Spinal; Cervical Vertebrae; Neck; Neck Pain; Nervous System Physiological Phenomena